LabDisk for SAXS: a centrifugal microfluidic sample preparation platform for small-angle X-ray scattering. Issue 7 (2nd March 2016) - Schwemmer, Frank; Blanchet, Clement E.; Spilotros, Alessandro; Kosse, Dominique; Zehnle, Steffen; Mertens, Haydyn D. T.; Graewert, Melissa A.; Rössle, Manfred; Paust, Nils; Svergun, Dmitri I.; von Stetten, Felix; Zengerle, Roland; et al.
Abstract : We present a centrifugal microfluidic LabDisk for protein structure analysis via small-angle X-ray scattering (SAXS) on synchrotron beamlines. Abstract : We present a centrifugal microfluidic LabDisk for protein structure analysis via small-angle X-ray scattering (SAXS) on synchrotron beamlines. One LabDisk prepares 120 different measurement conditions, grouped into six dilution matrices. Each dilution matrix: (1) features automatic generation of 20 different measurement conditions from three input liquids and (2) requires only 2.5 μl of protein solution, which corresponds to a tenfold reduction in sample volume in comparison to the state of the art. Total hands on time for preparation of 120 different measurement conditions is less than 5 min. Read-out is performed on disk within the synchrotron beamline P12 at EMBL Hamburg (PETRA III, DESY). We demonstrate: (1) aliquoting of 40 nl aliquots for five different liquids typically used in SAXS and (2) confirm fluidic performance of aliquoting, merging, mixing and read-out from SAXS experiments (2.7–4.4% CV of protein concentration). We apply the LabDisk for SAXS for basic analysis methods, such as measurement of the radius of gyration, and advanced analysis methods, such as the ab initio calculation of 3D models. The suitability of the LabDisk for SAXS for protein structure analysis under different environmental conditions is demonstrated for glucose isomerase under varying protein and NaCl concentrations. We show that the apparent radius of gyration of the negatively charged glucose isomerase decreases with increasing protein concentration at low salt concentration. At high salt concentration the radius of gyration ( R g ) does not change with protein concentrations. Such experiments can be performed by a non-expert, since the LabDisk for SAXS does not require attachment of tubings or pumps and can be filled with regular pipettes. The new platform has the potential to introduce routine high-throughput SAXS screening of protein structures with minimal input volumes to the regular operation of synchrotron beamlines.